BOWEL OBSTRUCTION DUE TO SIGMOID COLON ENTRAPMENT TO INTRAUTERINE AFTER CURETTAGE PROCEDURE - Rahmatullah, Andika Ilham; Purwohadi, Wahyu (Ahmad Dahlan Medical Journal, 2026)
Uterine perforation represents an uncommon yet potentially severe complication of uterine curettage, as it may involve intra-abdominal organs and result in life-threatening outcomes. Timely identification and appropriate management are essential to prevent serious morbidity. We report a 37-year-old woman who presented with abdominal distension, inability to pass gas, and absence of defecation three days after undergoing uterine curettage for retained placenta. Abdominal X-ray suggested large bowel obstruction. Exploratory laparotomy revealed sigmoid colon entrapment within a uterine perforation. The bowel was viable and successfully reduced, followed by uterine repair. The patient had an uneventful recovery and was discharged in good condition. Uterine perforation can manifest with delayed and nonspecific clinical signs, making diagnosis challenging. While the small intestine is more frequently affected, the occurrence of sigmoid colon entrapment within a uterine defect is exceptionally uncommon. Diagnostic imaging, particularly computed tomography (CT), can assist in identifying the condition; nevertheless, surgical exploration remains the gold standard for establishing the diagnosis and providing definitive management. This case highlights the need to consider uterine perforation accompanied by bowel incarceration in patients who develop bowel obstruction symptoms following curettage. Prompt diagnosis and early surgical management are essential to minimize complications and ensure optimal patient outcomes.